Cardiac autonomic modulation adjustments in isometric exercise - António,Ana Márcia dos Santos (2015)
OBJECTIVE: Isometric exercise is characterized by promoting an overload on the cardiovascular system due to pulsatile contraction followed by a significant increase in muscle blood flow. The hemodynamic responses during exercise and during recovery from endurance exercise are well documented. However, there are few studies with hard data regarding the influence of isometric exercise on autonomic control, which can be obtained by analysis of heart rate variability. Thus, the object of this study was to analyze reports on cardiac autonomic regulation in isometric exercise. METHODS: The articles used in this study were selected fromPubmed, PEDro,Medline, Lilacs and SciELO. The search wasmade by crossing the following keywords: isometric exercise, autonomic nervous system, cardiovascular system, and heart rate variability, which were defined based on descriptors of Health Headings (MeSH). RESULTS: The search provided 17 articles in isometric exercise autonomic modulation characterized by decreased vagalmodulation followedby increased sympatheticmodulation and its reversal shortly after the endof the activity. CONCLUSION: During isometric exercise, increased sympathetic modulation and reduced vagal modulation of the sinus node have been reported.